ОТНОШЕНИЕ СТУДЕНТОВ К ЗДОРОВЬЮ И ЛЕЧЕНИЮ ПО МЕРЕ ОБУЧЕНИЯ В СВЯЗИ С УРОВНЕМ ФИЗИЧЕСКОЙ ПОДГОТОВЛЕННОСТИ. - Evdokimov I. M. (Socio-Pedagogical Issues of Education and Upbringing, 2021)
The attitude to the issues of health and treatment of students is of indisputable interest. The attitude of society to health as an actual value, and therefore to the treatment of diseases, their prevention and healthy lifestyle, significantly depends on what views they themselves, as future specialists, have, and what they will transmit in their work. The state of health of students largely depends on their physical condition, is reflected in various kinds of sensory and emotional experiences, causes a wide range of positively or negatively colored mental states.
Keywords: здоровье; профилактика; физическое состояние; психические состояния; mental states; prevention; health; лечение болезней; treatment of diseases; physical condition